Lanreotide for the treatment of gastroenteropancreatic neuroendocrine tumors. (11th February 2016) - Saif, Muhammad Wasif
ABSTRACT: Introduction : The prevalence of gastropancreatic neuroendocrine tumors (GEP-NETs), a largely sporadically occurring group of neoplasms, has rapidly increased. NET diagnoses often occur late and entail treatment challenges; treatment beyond surgical resection is typically required. Somatostatin analogs (SSAs), the cornerstone of GEP-NET therapy, target somatostatin receptors on NET cell surfaces and can ameliorate NET-related symptoms and prevent tumor progression. Areas c overed : This expert review summarizes the development of the SSA lanreotide and its role in treating NETs. Key lanreotide preclinical and clinical findings in acromegaly, carcinoid syndrome, and NETs are discussed, along with future treatment goals and therapeutic prospects. Expert o pinion : The role of SSAs in NET treatment was historically one of symptom management. Although this is a critical therapeutic component, ideal treatment would include prevention of tumor progression. As GEP-NETs are biologically diverse, progression prevention can be difficult, depending on primary tumor site and functional status. Recent data indicate that lanreotide significantly prolonged progression-free survival in metastatic GEP-NET patients. Practice patterns seem to be shifting toward using SSAs as first-line therapy. Response to SSAs has typically been categorized as either symptomatic or biochemical. However, SSA use to prevent tumor progression will lead to a new, objective response category based on tumor growth.